Convergence in tourism management research: a bibliometric analysis - Cristina Estevão; Ana Rita Garcia; Sara Brito Filipe; Cristina Fernandes (Tourism & Management Studies, 2017)
The tourism sector has correspondingly attracted a great deal of interest from many researchers with particular focuses falling on tourismmanagement and witnessing exponential growth in the research on this field. Given this, the objective of this current study involves producing a chart of these scientific publications, identifying their intellectual structure and the research trends in tourism management. Our research thus seeks to contribute towards: (i) mapping the intellectual structure of research on tourism management as depicted in the academic literature, (ii) identifying the fundamental contributions made by the tourism management research field, (iii) determining the lines of research constituting its intellectual structure, (iv) identifying the scientific journals with the greatest impact on this area and (v) identifying the geographic distribution of knowledge, by universities and countries, and the collaborative structures.